A multicenter cohort study of primary hypertension in Korea: study design and interim analysis of the Korean registry of target organ damage in hypertension (KorHR) - Suk-Won Choi; Seong Woo Han; Jong Sun Ok; Byung-Su Yoo; Mi-Seung Shin; Sung Ha Park; Kyu-Hyung Ryu (BMC, 2017)
Abstract Background The Korean Registry of Target Organ Damage in Hypertension aims to evaluate the clinical characteristics and prevalence of subclinical target organ damage in Korean hypertensive patients. Method This is a prospective, observational, multicenter cohort study in which 23 university hospitals participated. Since May 2013, we have enrolled 1,318 consecutive hypertensive patients without known cardiovascular disease who met the following inclusion criteria: 1) age older than 30 years and 2) the first visit to the participating hospitals was within the last 5 years. Results The mean age was 52 ± 12 years; 62.1% were male, and 41.3% were incident hypertensives. Patients with diabetes mellitus accounted for 7.8% of the population and 43.8% had hyperlipidemia or were on statins at baseline. The mean office blood pressures were 152 ± 20/96 ± 14 mmHg for incident hypertensive patients and 129 ± 13/78 ± 10 mmHg for patients on treatment. Patients with electrocardiographic and echocardiographic left ventricular hypertrophy accounted for 18.9 and 25.6%, respectively. The mean brachial-ankle pulse wave velocity (PWV) was 1564 ± 293 m/s and 19.5% had PWV values of more than 1750 cm/s. Patients with microalbuminuria and chronic kidney disease accounted for 21 and 4%, respectively. The first prescribed class of antihypertensive medications was angiotensin converting enzyme inhibitors in 2.9%, angiotensin receptor blockers (ARBs) in 57.5%, diuretics in 7.6%, calcium channel blockers (CCBs) in 61.0%, beta blockers in 17.3%, and fixed dose combination pill in 27.8%. Conclusion Our interim analysis shows that subclinical target organ damage in hypertension is considerably present for incident or treated hypertensive patients. CCBs and ARBs were the most commonly prescribed classes of antihypertensive medications and fixed dose combination pills were actively used in Korea. Trial registration NCT01861080 . Registered 16 May 2013